Combretastatin A-4: The Antitubulin Agent that Inspired the Design and Synthesis of Styrene and Spiroisatin Hybrids as Promising Cytotoxic, Antifungal and Antiviral Compounds (2020)
ABSTRACT: The design of a series of styrene and spiroisatin hybrids was based on the structure of combretastatin A-4 1. This library of 20 compounds were synthesized with the pharmacophoric units: 3,4,5-trimethoxy or/and 4-hydroxy-3-methoxy phenyl moities in their structure. Thereby, the libraries of β-nitrostyrenes 10a-10c, spiroisatin-dihydroquinolines 14a-14c, spiroisatinthiazolidinones 17a-17c and spiroisatin-nitropyrrolizidines 20a-20k were evaluated for their in vitro cytotoxic, anti-proliferative, antifungal and antiviral activities. Biological results revealed that among these compounds, β-nitrostyrenes 10a-10c exhibited significant cytotoxicity (HeLa and Jurkat tumor cells) and antifungal (T. mentagrophytes) activities. Moreover, the spiroisatindihydroquinoline 14a and 14c showed promising cytotoxicity (U937 cells). 14a-14c molecules were active against human herpesviruses serotypes 1 and 2 (HHV-1 and HHV-2), but only 14a and 14b were effective against dengue virus serotype 2 (DENV-2). The spiroisatin-nitropyrrolizidine 20c exhibited moderate anti-herpetic activity, while 17c spiroisatin-thiazolidinone derivative also reduced the infection of HHV-1 and DENV-2. Finally, the molecular docking showed that these kind of molecules interact with the subunit α/β-tubulin.